Safflower Polysaccharide Inhibits AOM/DSS-Induced Mice Colorectal Cancer Through the Regulation of Macrophage Polarization - Wang, Qun; Huang, Yun; Jia, Min; Lu, Dong; Zhang, Hong-Wei; Huang, Dan; Liu, San-Hong; Lv, Chao (Frontiers in Pharmacology, 2021)
Safflower polysaccharide (SPS) is one of the active fraction extracted from safflower petals (Carthamus tinctorius L.), which has been reported to possess anti-tumor and immune control role. However, its anti-tumor mechanisms by regulating the immune pathway remains barely understood. In this study, a mouse model was established by azoxymethane (AOM)/dextran sodium sulfate (DSS) to evaluate the anti-tumor effect of SPS on colorectal cancer (CRC). The results showed that 50 mg/kg SPS-1, an active fraction isolated from SPS, could significantly inhibit CRC induced by AOM/DSS, and changed the polarization of macrophages to M1 phenotype. Meanwhile, SPS-1 treatment significantly alleviated the characteristic AOM/DSS-induced pathological symptoms, in terms of decreased nucleoplasmic ratio, nuclear polarity extinction, and gland hyperplasia. However, the results in vitro showed that SPS-1 did not directly inhibit the growth of CRC cells, but could up-regulate the NF-κB signal and trigger M1 macrophage transformation. Thus, the condition medium (CM) of Mφ pretreated with SPS-1 was used to against CRC cells. As expected, SPS-1-activated Raw264.7 markedly exhibited anti-tumor effects by inhibiting cell proliferation and suppressing cell colony formation. In addition, SPS-1-activated Raw264.7 also could induce CRC cell apoptosis by up-regulating the levels of tumor necrosis factor-α (TNF-α) and nitric oxide (NO). Further results suggested that SPS-1-induced transition of macrophage phenotype could be suppressed by a NF-κB inhibitor PDTC. Moreover, SPS-1-activated Raw264.7 inhibiting CRC cells proliferation and inducing apoptosis were also rescued by PDTC. Taken together, all results suggested that SPS-1 could be a therapeutic option for the prevention and treatment of CRC.